Effect of diet based on the principles of Iranian traditional medicine on cirrhosis (a clinical trial). (December 2016) - Ehsani, Mohammad Javad; Mahdavi Jafari, Jamileh; Aliasl, Jale; Kamalinejad, Mohammad; Gachkar, Latif; Choopani, Rasool
Highlights: ITM resulted in weight reduction mostly in overweight subjects. ITM resulted in increased albumin in cirhhotic patients in weight gain group. ITM resulted in reduced AST in cirrhotic patients who lost weight. ITM was beneficial for subjects who either gained weight and those who lost weight. Abstract: Objectives: Cirrhosis is associated with morbidity and mortality worldwide. Iranian traditional medicine (ITM) focused on nutritional intervention in order to improve liver function. The aim of this study was to assess the effectiveness of a diet designed based on ITM and current dietary recommendations. Design: This controlled trial study was performed on 57 subjects with cirrhosis in 5 tertiary hospitals in Teharn, Iran. Setting: Subjects were included if they were diagnosed with class A or B cirrhosis between October 2013 and December 2014. Interventions: Subjects were randomly allocated into intervention (28 subjects) who received dietary and lifestyle recommendations based on ITM and controls (29 subjects) who received routine dietary and lifestyle recommendations for 3 months. Subjects were assessed at baseline and at the end of the intervention for anthropometric measures, liver function tests and cirrhosis severity scoring. Main outcome measures: Model for End-Stage Liver Disease (MELD), anthropometric measures, serum albumin, liver function tests, International Normalized Ratio and alkaline phosphatase as well as subjective findings. Results: Mean age of the subjects was 51.19 ± 11.88 years. Weight reduction was observed in 41 subjects (22 subjects in intervention and 19 in control group). Dietary intervention resulted in a significant decrease in alanine aminotransferase (AST) (p = 0.04) and significant resolution of icterus in sclera (p = 0.02) in weight loss group and increase serum albumin in weight gain group (p = 0.02). Conclusions: ITM recommendations could be beneficial for cirrhotic patients both for the purpose of weight reduction and weight gain.